Enantioselective dearomative ortho-cycloaddition transformation of unactivated arenes by cage-confined visible-light photocatalysis - Yang, Jie; Li, Zhongshu; Wu, Xiantao; Chen, Jie; Huang, Sisi; Lu, Yu-Lin; Jiao, Zhiwei; Su, Cheng-Yong (Nature communications, 2025)
Photoinduced dearomatization of arenes is a powerful strategy in organic synthesis to disrupt the stable aromaticity; however, the asymmetric dearomatization photocatalysis of unactivated arenes remains highly challenging and rare. Herein we demonstrate an enzyme-mimicking cage-confined visible-light asymmetric photocatalysis method for intramolecular dearomative cycloaddition with electron-deficient β -aryl enones. Owing to the multi-functional synergy of chirality, energy transfer, and host-guest interactions in the confined microenvironments, the self-assembled chiral cage-photoreactor could pre-organize the arenes and activate the β -aryl enones to give stereoselectively fused cyclobutanes through visible-light induced [2 + 2] ortho -cycloaddition. Notably, the competing transformation to stable [4 + 2] cycloadducts has been inhibited, producing thermodynamically unfavorable [2 + 2] cycloadducts with excellent regio-, diastereo-, and enantioselectivities. The asymmetric dearomatization photocatalysis of unactivated arenes remains challenging and rare. Herein the authors demonstrate an enzyme‐mimicking cage‐confined visible‐light asymmetric photocatalysis method for intramolecular dearomative cycloaddition with electron‐deficient β‐aryl enones.